2010
DOI: 10.1051/apido/2010017
|View full text |Cite
|
Sign up to set email alerts
|

Varroamites and honey bee health: canVarroaexplain part of the colony losses?

Abstract: -Since 2006, disastrous colony losses have been reported in Europe and North America. The causes of the losses were not readily apparent and have been attributed to overwintering mortalities and to a new phenomenon called Colony Collapse Disorder. Most scientists agree that there is no single explanation for the extensive colony losses but that interactions between different stresses are involved. As the presence of Varroa in each colony places an important pressure on bee health, we here address the question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
374
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(389 citation statements)
references
References 89 publications
(81 reference statements)
2
374
0
13
Order By: Relevance
“…In central European countries, honeybee colonies are considered in danger of collapsing due to Varroa once natural mite fall goes beyond ten mites per day (Le Conte et al 2010). However, none of the colonies showed any signs that they were close to collapsing, suggesting that the damage threshold is higher in A. m. scutellata.…”
Section: Discussionmentioning
confidence: 99%
“…In central European countries, honeybee colonies are considered in danger of collapsing due to Varroa once natural mite fall goes beyond ten mites per day (Le Conte et al 2010). However, none of the colonies showed any signs that they were close to collapsing, suggesting that the damage threshold is higher in A. m. scutellata.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, dramatic losses of managed honey bee colonies have been reported in Europe and North America over the past decade (vanEngelsdorp et al 2009, Genersch et al 2010, Neumann and Carreck 2010, Potts et al 2010 JEVROSIMA STEVANOVIC et al Ellis et al 2010). As no single explanation for the extensive colony losses has been identified, it is concluded that many biological and environmental stressors, acting alone or in combination, can lead to premature colony mortality (vanEngelsdorp et al 2009, Genersch 2010.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%
“…The health of honeybees has been one of the most important topics in apicultural research in recent years (Genersch, 2010). This is primarily due to the recent emergence of high honeybee colony losses in many parts of the world (Le Conte et al, 2010;Neumann and Carreck, 2010;Stokstad, 2007;vanEngelsdorp et al, 2008) and the vulnerability of honeybees to parasitic mites, fungi, viruses and bacteria (Bailey and Ball, 1991;Chen et al, 2006;Dietemann et al, 2012;Genersch, 2010;Genersch et al, 2010;Martin, 2001;Ribière et al, 2010;Sammataro et al, 2000). These pathogens and parasites can have harmful effects on honeybee health and the services they offer, which in turn can lead to severe economic losses (Genersch, 2010;Morse and Calderone, 2000;Shen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%